'Beyond Human Ownership'? Property, Power and Legal Personality for Nature in Aotearoa New Zealand. (20th November 2017) - Sanders, Katherine
ABSTRACT: In 2014, Te Urewera, land formerly comprising a national park in Aotearoa New Zealand, was declared a legal entity. In 2017, the Whanganui River was declared a legal person. This article analyses the grant of legal personality as part of a process that seeks to acknowledge colonial wrongs to hapū and iwi, indigenous descent groups. It argues that a primary purpose of the grant is to regulate human relationships. Legal personality recognises the competing claims of the Crown and hapū and iwi to political authority and allows for the establishment of new legal frameworks, which address who is entitled to act on behalf of the land and river. The article concludes that the settlements should be regarded as constitutional in nature—the grant of legal personality provides a forum for disagreement and compromise, and the opportunity for relationships between peoples, land and authority to be reframed.